Comprehensive Assessment of Health System Performance in Odisha, India. Issue 1 (1st January 2022) - Yip, Winnie; Kalita, Anuska; Bose, Bijetri; Cooper, Jan; Haakenstad, Annie; Hsiao, William; Woskie, Liana; Reich, Michael R.
ABSTRACT: India has recently implemented several major health care reforms at national and state levels, yet the nation continues to face significant challenges in achieving better health system performance. These challenges are particularly daunting in India's poorer states, like Odisha. The first step toward overcoming these challenges is to understand their root causes. Toward this end, the Harvard T.H. Chan School of Public Health conducted a comprehensive study in Odisha based on ten new field surveys of the system's performance to provide a multi-perspective analysis. This article reports on the assessment of the performance of Odisha's health system and the preliminary diagnosis of underlying causes of the strengths and challenges. This comprehensive health system assessment is aimed toward the overarching goals of informing and supporting efforts to improve the performance of health systems in Odisha and other similar contexts.